USING INTERNET AND TRAVEL AGENCIES IN PLANNING A TRIP. A QUALITATIVE APPROACH - Oana Tugulea; Claudia Bobalca; Andreea Maha; Liviu-George Maha (CES Working Papers, 2014)
The purpose of the present research is to discover and to understand young people’s touristic behaviour. We investigated the process of planning a trip, the perception about travel agencies and about Internet using qualitative methods. The aim of this paper is also to establish how important are qualitative methods when trying to understand touristic behaviour. We used exploratory qualitative research. Even we made only a qualitative research there are some managerial implications of this study. Managers must focus on human factor when promoting a touristic product. They can use Internet to inform young tourists but they must understand the importance of presenting the real conditions and not an improved option of the real offer. Travel agencies must be as flexible as the situation allows. This paper is important because it investigates in-depth the young tourists opinions and allow a comparison between the perception on travel agencies and the Internet.